Media Pembelajaran Prototype Pembuatan Sistem Kontrol dan Monitoring Runway Edge Light Panel Surya Berbasis GSM - Rifqi Raza Bunahri; Jemi Victor Palpialy; Nikolas Makanuay; Danang Dimastiar; Kurniawan Adi Saputro; M. Hasrul; Nur Aini Fadilla (Politeknik Penerbangan Jayapura, 2024)
The unavailability of learning media requires Jayapura Aviation Polytechnic students to visit Sentani Airport to conduct practical learning. This research aims to develop and test GSM-based solar panel runway edge light tools as learning media. The research method uses a development approach with experiments in the form of testing control systems and monitoring tool performance. The results showed that this tool can adjust the light intensity as needed, save time and energy without requiring a visit to Sentani Airport. However, this tool has limitations because it depends on sunlight so it does not work when it rains. This tool can be an alternative learning media that is practical and effective in the field of aviation.